THE APPLICATION OF ROTATING TRIO EXCHANGE STRATEGY TO IMPROVE SKILLS THINKING AND STUDENT ACHIEVEMENT (Study at natural science of grade V Student Elementary School Cluster 2 Lebong) - Ryan Permana Kusuma; Turdjai Turdjai (DIADIK, 2019)
This research aims to describe the improvement of thinking skills and learning achievement of the fifth grade students of SDN Cluster II North Lebong Lebong Regency. This research is a Classroom Action Research (CAR) combined with quasi-experiment. Subjects in this study were fifth grade students of SDN Group II North Lebong 2018/2019 academic year which amounted to 84 students of 53 male students and 31 female students from  67 Lebong Elementary Schools, SDN 20 Lebong and SD 58 Lebong.    The object of this research is the thinking skills and student achievement in the subject of Natural Sciences (IPA). Retrieval of research data using observation and test sheets. The results of this study indicate that the adoption of the Rotating Trio Exchange strategy can improve students' thinking skills and learning achievement in each cycle.